A Comparative Study On Students' Achievement Taught Present Continuous Tense By Using Dialogue And Reading Passage At The Second Year Of SMPN 2 Banyudono In 2012/2013 Academic Year - Widayanti, Dian; , Drs. Djoko Srijono, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This study is aimed at comparing the result of teaching present continuous tense taught by using dialogues and reading passage. The population of this study is second year students of SMP N 2 Banyudono in2012/2013 academic year. To take sample the writer used random sampling technique. The writer took two classes for this research, students taught by using dialogues is applied in class VIII C and students taught by using reading passage is applied in class VIII D. Each class consists of 30 students. After getting the required data, the writer compared the scores of the graphs by using t-test formula. The mean of two groups is measured from the different scores of post-test and pre-test from all of the students and then divided to the population of each groups. From the computation of t-test value, it is known that is 2.4, whereas from the degree of freedom 58 is 1.697. Its means that is higher that (2.4 > 1.697). From the result of the study, it is known that there is significant difference in students' achievement present continuous tense taught by using dialogues and reading passage is accepted. The second hypothesis shows that the students taught by using dialogues have better than taught by using reading passage.